INDONESIAN USER PERCEPTION ON THE USEFULNESS OF AUTO-TRANSLATE FEATURE ON SOCIAL MEDIA - Annissa Manystighosa; Esti Junining; Roosi Rusmawati (UIBU, 2022)
This paper focuses on the user perception of their experience in using the auto-translate feature on social media. A mixed-method is employed in this study to gain quantitative and qualitative results and provide a more in-depth understanding of the analysis, with an online questionnaire as the research instrument. In order to reach a broader audience, snowball sampling is used since there are no specific criteria for the subject target. The majority of the respondents are women with bachelor's degrees aged 17-28. There are three aspects of assessment on the questionnaire following Nababan’s theory: accuracy, acceptability, and readability. The findings showed that the result of the auto-translate feature on social media has good accuracy, moderate readability, and is very acceptable. Meanwhile, the shortcomings of this feature are lack of context understanding, mistranslation due to wrong diction, and grammar updates.